(untitled) (Research, Society and Development, 2020)
Cannabinoid compounds have therapeutic properties, but also psychotropic effects. Cannabidiol (CBD) extracted from Cannabis sativa has been used in cases of epilepsy, a disorder that occurs in the brain caused by genetic predisposition, as in West Syndrome. Epilepsies and their symptoms can cause neurobiological, cognitive and psychosocial consequences, especially when not treated in a timely manner and accompanied by a qualified professional. Given the above, the present study aims to conduct an integrative review, reporting a clinical case of a patient with West Syndrome, to assess the benefits of using cannabidiol in treatment of epilepsy. An integrative review was conducted based on research in electronic databases, and the clinical case was described. The administration of CBD had beneficial effects in the adjunctive treatment to other antiepileptics. The patient was treated with CBD for 7 months and improvements in interaction were found, she had greater perception and smarter interaction with the world around her. It is essential that a trained professional who understands the subject accompanies the patient in each progression or regression of the dose for crisis control. There is still a lot to study about the use of CBD in the treatment of epilepsy, and also about West Syndrome, because the effects of CBD depend a lot on the organism and the type of crisis of each patient.